2017
DOI: 10.1080/20426445.2016.1241912
|View full text |Cite
|
Sign up to set email alerts
|

A new method for defect detection in lumber images: optimising the energy model by an irregular parametric genetic approach

Abstract: Accurate detection of surface defects plays a vital role in automated analysis of lumber quality in the wood industries. A new method, based on a genetic optimisation of energy model, is introduced here for defect detection in lumber images. In this method, a hypothesis testing framework is defined, first to separate defects from natural tissue of lumber. Then, the boundary of lumber is estimated by a decision function based on the energy optimisation method which is driven by an irregular parametric genetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…By comparing the results of all models, we found that the number of filters strongly affects the accuracy of the model. Fewer filters can effectively decrease the FLOPs but the accuracy also decreases, which is not acceptable for wood defect detection in our study, even though the accuracy is more than 90% [47]. The kernel size also slightly affects the accuracy of the model but it has a strong effect on the FLOPs, as found by comparing Models 4 and 5.…”
Section: Glance Network Searched Structurementioning
confidence: 55%
“…By comparing the results of all models, we found that the number of filters strongly affects the accuracy of the model. Fewer filters can effectively decrease the FLOPs but the accuracy also decreases, which is not acceptable for wood defect detection in our study, even though the accuracy is more than 90% [47]. The kernel size also slightly affects the accuracy of the model but it has a strong effect on the FLOPs, as found by comparing Models 4 and 5.…”
Section: Glance Network Searched Structurementioning
confidence: 55%